Ethylcellulose - a pharmaceutical excipient with multidirectional application to be utilized in the pharmaceutical technology - Katarzyna Olechno (Polish Pharmaceutical Society, 2022)
Synthetic polymers, biopolymers and their modified derivatives are widely used in medicine and pharmacy. They play a significant role in the development of drug dosage forms serving as carriers of therapeutic substances, ensuring modified drug release or masking bitter taste of medicines. Polymers of natural, semi-synthetic and synthetic origin are used. They are characterized by a variety of physicochemical properties, which depend, among others, on their molecular weight or spatial configuration. Among polymers used in pharmaceutical technology, polysaccharides, which include e.g. derivatives of cellulose, are of significant importance. Cellulose is the polymer most commonly found in nature. It is produced during photosynthesis and constitutes the basic material of plant organisms. The raw material is a linear polymer consisting of glucopyranose residues whose units are connected by 1,4β-glycosidic bonds. It occurs as an odourless and tasteless powder with a fibrous structure which is practically insoluble in both hot and cold water. Among the modified derivatives of cellulose, its esters and ethers are of practical importance, such as methylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose and ethylcellulose. The monographs of the European Pharmacopoeia (Ph. Eur.) and the United States Pharmacopoeia (USP) define the material as partially O-ethylated cellulose. Ethylcellulose is a biocompatible, non-allergenic and non-irritating hydrophobic polymer that is recognised as a safe excipient approved by the Food and Drug Administration (FDA) to be used in oral and topical formulations. Different grades of ethylcellulose are available, which differ in their degree of polymerisation and degree of etherification. The aim of this article was to provide a broad overview of the utilization of ethylcellulose for pharmaceutical purposes, with particular emphasis on its role in the development of oral and topical formulations. The paper is a review of both commercially available products in the manufacture of which ethylcellulose is used, as well as scientific achievements in the design of new drug delivery systems utilizing ethylcellulose.